A Plant-Produced in vivo deglycosylated full-length Pfs48/45 as a Transmission-Blocking Vaccine Candidate against malaria - Tarlan Mamedov (Nature Portfolio, 2019)
Abstract Pfs48/45 is a leading antigen candidate for a transmission blocking (TB) vaccine. However, efforts to produce affordable, safe and correctly folded full-length Pfs48/45 using different protein expression systems have not produced an antigen with satisfactory TB activity. Pfs48/45 has 16 cysteines involved in disulfide bond formation, and the correct formation is critical for proper folding and induction of TB antibodies. Moreover, Pfs48⁄45 is not a glycoprotein in the native hosts, but contains potential glycosylation sites, which are aberrantly glycosylated during expression in eukaryotic systems. Here, we demonstrate for the first time that full length, Endo H in vivo enzymatic deglycosylated Pfs48/45 antigen is produced at a high level in plants and is structurally stable at elevated temperatures. Sera from mice immunized with this antigen showed strong inhibition in SMFA. Thus, Endo H in vivo enzymatic deglycosylated Pfs48/45 is a promising candidate for the development of an affordable TB vaccine, which may have the potential to save millions.